If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(3x + 5) = 22 Reorder the terms: 6x + -1(5 + 3x) = 22 6x + (5 * -1 + 3x * -1) = 22 6x + (-5 + -3x) = 22 Reorder the terms: -5 + 6x + -3x = 22 Combine like terms: 6x + -3x = 3x -5 + 3x = 22 Solving -5 + 3x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3x = 22 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 22 + 5 3x = 22 + 5 Combine like terms: 22 + 5 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| -6(p+5)=-16-8p | | 2+8x=20-x | | -8k+ra=r-2y | | -8k+ar=r-2y | | 4/6=m/9 | | -18=6(6x+3)+4(x-9) | | 3r-4r+1r=-12 | | .666.....x+5=.666...+14 | | -3(3-8k)=-8k+23 | | -2y^2+3y+5= | | -(3x+7)=-8-4x | | 14+14= | | AB+CD=E | | .3333.....x+5=.333...+14 | | 3(3x+7)=-8-4x | | m+3m+5m=-9 | | x-12=4x+21 | | 7y-2=2y-20 | | -5+7v=6(6v+4) | | 0=2x+3x | | 3(2x-8)-5(15-6x)=9(4x-11) | | 10x+22=-2(x+5) | | 61=-9(v-9)+3(-6+3v) | | 8(k+8)=3k+29 | | 6k+6k=12 | | 5d+54=89 | | 7-7(n+5)=-24-8n | | -7n-5=-5(n-1) | | 9r-5r-6r= | | -3x-1x=-12 | | 3x-12=2(5x-10) | | 14+x=6-x |